Personalizing antipsychotic treatment: evidence and thoughts on individualized tailoring of antipsychotic dosage in the treatment of psychotic disorders. (April 2019) - Wunderink, Lex
Effectiveness of relapse prevention with antipsychotic drugs has been robustly demonstrated. However, the drawbacks of antipsychotic maintenance treatment have prompted alternative strategies to reduce antipsychotic load. A prominent drawback of antipsychotics is their negative impact on subjective well-being, initiative, and drive related to dopamine D2 blockade. This might compromise functional capacity. First-episode studies from 1980 to 2018, including relevant reviews and meta-analyses, are evaluated, showing a lack of functional outcome data. In addition to relapse rates, which is the primary outcome in the great majority of studies, long-term functional outcome is pivotal, because these two outcome domains may point in opposite directions. The trade-off between relapse rates and functional outcome is discussed by our 2013 dose-reduction study. We conclude that divergent outcomes and various individual risk-profiles preclude the construction of a generic outcome measure. The relationship of relapse and functional outcome is considered, as well as the conceivable role of negative symptoms and some related issues. Future profiling of individual risk/benefit characteristics combined with personal preferences may offer better guidance in antipsychotic pharmacotherapy. More studies are needed to elucidate individual risk profiles, predictive of functional capacity and relapse rates, to draw differential conclusions on long-term risks and benefits of antipsychotics across the spectrum of psychosis.